Impact of pre-existent vascular and poly-vascular disease on acute myocardial infarction management and outcomes: An analysis of 2 million patients from the National Inpatient Sample. (15th March 2021) - Kobo, Ofer; Contractor, Tahmeed; Mohamed, Mohamed O.; Parwani, Purvi; Paul, Timir K.; Ghosh, Raktim K.; Alraes, M. Chadi; Patel, Brijesh; Osman, Mohammed; Ludwig, Josef; Roguin, Ariel; Mamas, Mamas A.
Abstract: Background: Patients with pre-existing vascular disease are known to have worse outcomes after acute myocardial infarction (AMI). However, there is limited data for outcomes stratified by type and number of vascular territories involved. Methods: Using the Nationwide Inpatient Sample (2015–2017), we examined outcomes of AMI in patients with pre-existent vascular disease stratified by number as well as types of diseased beds including all five major vascular sites: cardiac, cerebrovascular, renal, aortic and peripheral vascular disease (PVD). Multivariable logistic regression was used to determine the adjusted odds ratios (aOR) of adverse outcomes and invasive procedure utilization. Results: Out of 2, 184, 614 AMI admissions, 49.7% had pre-existent vascular disease. The odds of major adverse cardiovascular and cerebrovascular events (MACCE), mortality, ischemic stroke and major bleeding incrementally increased and was highest in those with ≥3 vascular sites involved (aOR for MACCE 1.16, CI 1.13–1.19; mortality 1.3, CI 1.26–1.34; stroke 1.15, CI 1.1–1.2; major bleeding 1.21, CI 1.16–1.25). Amongst those with a single pre-existent diseased vascular bed, the adjusted odds of MACCE appeared to be higher in those with PVD (1.28, CI 1.26–1.31), aortic disease (1.24, CI 1.19–1.29), and cerebrovascular disease (1.22, CI 1.2–1.25). Patients with pre-existent vascular disease had a lower overall likelihood of undergoing invasive revascularization procedures. Conclusions: Approximately half of the population presenting with AMI have pre-existent vascular disease. There is an incremental increase in adverse outcomes with increasing number of diseased vascular beds, with further differences in outcomes and utilization of invasive procedures based on sub-types of sites involved. Graphical abstract: Unlabelled Image Highlights: Approximately half of the population presenting with AMI have pre-existent vascular disease. Incremental increase in adverse outcomes with increasing number of diseased vascular beds Patients with pre-existent vascular disease had a lower likelihood of undergoing invasive revascularization procedures Higher odds of MACCE in patients with PVD, aortic disease, and cerebrovascular disease Highest amongst patients with PVD